Implementasi Sistem Informasi Penggajian Untuk Membantu Manajemen Keuangan Dalam Pengolahan Usaha - Mira Susanti; Rasman Hidayatullah (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
The era of globalization also affects the business environment in data processing in the form of transactions such as payroll. If the process of payroll calculation is slow and prone to error can lead to discontinuity between employees and management and the use of conventional systems also lead to data security is not guaranteed then the required system that supports management needs in the form of payroll information system to minimize errors that can be used in decision making and influence to smooth business. The method used is the System Development Life Cycle (SDLC) which is a guide in designing and developing information systems. Implemented payroll information systems are able to generate accurate payroll reports in the form of loan evidence, employee salary recaps making it easier to control profits-related businesses to create sound financial management.